2012
DOI: 10.1099/ijs.0.024349-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Anaerobaculum hydrogeniformans sp. nov., an anaerobe that produces hydrogen from glucose, and emended description of the genus Anaerobaculum

Abstract: A novel anaerobic, moderately thermophilic, NaCl-requiring fermentative bacterium, strain OS1T, was isolated from oil production water collected from Alaska, USA. Cells were Gram-negative, non-motile, non-spore-forming rods (1.7–2.7 × 0.4–0.5 µm). The G+C content of the genomic DNA of strain OS1T was 46.6 mol%. The optimum temperature, pH and NaCl concentration for growth of strain OS1T were 55 °C, pH 7 and 10 g l−1, respectively. The bacterium fermented d-fructose, d-glucose, maltose, d-mannose, α-ketoglutara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 49 publications
3
48
0
1
Order By: Relevance
“…EF559200), from a T and related genera of the phylum Synergistetes Taxa: 1, strain 4F6E T (data from this study); 2, Aminiphilus (Díaz et al, 2007); 3, Aminobacterium (unless indicated, data from Baena et al, 1998Baena et al, , 2000; 4, Aminomonas (Baena et al, 1999b); 5, Anaerobaculum (Rees et al, 1997;Menes & Muxí, 2002;Maune & Tanner, 2012); 6, Cloacibacillus (Ganesan et al, 2008); 7, Dethiosulfovibrio (unless indicated, data from Magot et al, 1997;Surkov et al, 2001;Díaz-Cárdenas et al, 2010);8, Fretibacterium (Vartoukian et al, 2013);9, Jonquetella (Jumas-Bilak et al, 2007); 10, Pyramidobacter (Downes et al, 2009);11, Synergistes (Allison et al, 1992); 12, Thermanaerovibrio (Guangsheng et al, 1992;Baena et al, 1999a;Zavarzina et al, 2000); 13, Thermovirga (Dahle & Birkeland, 2006). +, Positive; 2, negative; ND, no data available.…”
Section: Strain 4f6ementioning
confidence: 74%
See 1 more Smart Citation
“…EF559200), from a T and related genera of the phylum Synergistetes Taxa: 1, strain 4F6E T (data from this study); 2, Aminiphilus (Díaz et al, 2007); 3, Aminobacterium (unless indicated, data from Baena et al, 1998Baena et al, , 2000; 4, Aminomonas (Baena et al, 1999b); 5, Anaerobaculum (Rees et al, 1997;Menes & Muxí, 2002;Maune & Tanner, 2012); 6, Cloacibacillus (Ganesan et al, 2008); 7, Dethiosulfovibrio (unless indicated, data from Magot et al, 1997;Surkov et al, 2001;Díaz-Cárdenas et al, 2010);8, Fretibacterium (Vartoukian et al, 2013);9, Jonquetella (Jumas-Bilak et al, 2007); 10, Pyramidobacter (Downes et al, 2009);11, Synergistes (Allison et al, 1992); 12, Thermanaerovibrio (Guangsheng et al, 1992;Baena et al, 1999a;Zavarzina et al, 2000); 13, Thermovirga (Dahle & Birkeland, 2006). +, Positive; 2, negative; ND, no data available.…”
Section: Strain 4f6ementioning
confidence: 74%
“…Among species of the Synergistetes, carbohydrate utilization has been observed with Anaerobaculum thermoterrenum (Rees et al, 1997), Anaerobaculum mobile (Menes & Muxí, 2002) and Anaerobaculum hydrogeniformans (Maune & Tanner, 2012).…”
Section: Strain 4f6ementioning
confidence: 99%
“…Isolated from oil production water collected from Alaska, USA. The properties are as given by Maune & Tanner (2012). …”
Section: Emended Description Of Acetomicrobiummentioning
confidence: 99%
“…Its topology was also supported using the maximum-parsimony and maximum-likelihood methods. The results indicate that Acetomicrobium flavidum pertains to the family Synergistaceae, phylum Synergistetes, having Anaerobaculum mobile (99.9 % similarity) (Menes & Muxí, 2002), Anaerobaculum hydrogeniformans (96.8 % similarity) (Maune & Tanner, 2012) and Anaerobaculum thermoterrenum (96.4 % similarity) (Rees et al, 1997), as its closest phylogenetic relatives (Fig. 1).…”
mentioning
confidence: 96%
See 1 more Smart Citation